Efecto de los ejercicios cardiovascular en el sobrepeso de personas con escoliosis en el cantón Salitre, Guayas, Ecuador, 2021 - Ronquillo Olvera, Kathya Odalys (2021)
A cardiovascular exercise guide will be developed for people with overweight and scoliosis. The purpose of which is to provide them with security so that they are not afraid to perform these exercises and aggravate the degree of their pathology. Overweight is an increase in body weight that can be harmful to health, this is measured through the body mass index (BMI), which is a simple indicator of the relationship between weight and height that is frequently used to identify overweight in individuals. It is calculated by dividing a person's weight in kilos by the square of their height in meters (kg / m2). That is why the realization of the guide is important because it allows to benefit those who are overweight and scoliosis, so that they can lead a healthy life and an adequate body weight.